Considerations on environmental history and its impact on law - Foy Valencia, Pierre (2018)
The author, employing some basic premises of relations (between time, nature, Humanity and the Law), explores the development of Environmental Law as an autonomous discipline on its historical context.This work also considers the various theories and approaches that have arisen, delivering a fundamental general overview for the interested layman that wishes to undertake researches on this field.